Quantitative Structure Property Relationships of Curcumin Compounds and Its Derivatives as Potential Anticancer Agents against PCNA Receptors with Molecular Docking Method: Hubungan Kuantitatif Struktur Properti Senyawa Turunan Kurkumin sebagai Antikanker Potensial dengan Metode Penambatan Molekul terhadap Reseptor PCNA - Santoso, Chiara Nathalie; Sugiyanto Sugiyanto; Ani Riani Hasana (Berkala Ilmiah Kimia Farmasi, 2025)
Nowadays, cancer therapy has significant negative consequences on the body. Prevention of these adverse effects can be done by developing new drug compounds that targeted the Proliferating Cell Nuclear Antigen (PCNA) receptor. Natural compounds such as curcumin with their multitarget properties have the potential to bind to this receptor. This study tested the curcumin compound and several of its derivatives to bind to the PCNA receptor on cancer cells and then predicted the physicochemical properties that affect the curcumin derivative compounds. The in silico docking used AutoDock Vina, molecular docking was carried out to predict interaction energy (ΔG) of curcumin derivatives against PCNA compared with compound AOH1996. The physicochemical properties that affect ΔG are seen by analyzing the quantitative structure property relationship (QSPR). As a result, the curcumin derivatives Dihydroxytetrahydrocurcumin is predicted to have ΔG = -6.7 kcal / mol, while the native ligand AOH1996 is had ΔG = -7.2 kcal / mol. Molecular docking shows that the interaction energy of curcumin derivatives is not better than the AOH1996. The physicochemical parameters predicted to affect the interaction energy of curcumin compounds in binding to the PCNA receptor are lipid solubility and molecular weight. Applying the physicochemical properties found from the QSPR, further research can be conducted to develop curcumin compounds that are more suitable for the PCNA receptor.   Keywords:  Curcumin Derivatives, PCNA receptor, AOH1996, Molecular Docking, QSPR